Функции сложные, поэтому немного теории перед нахождением их производных:
![(u-v)'=u'v-uv'\\ (cx)'=c\\ (\frac{u}{v})'=\frac{u'v-uv'}{v^{2}}\\ (\sqrt{x})'=\frac{1}{2\sqrt{x}}\\ (cosx)'=-sinx\\ (u^{n})'=n\cdot u^{n-1}\cdot u'\\ (u-v)'=u'v-uv'\\ (cx)'=c\\ (\frac{u}{v})'=\frac{u'v-uv'}{v^{2}}\\ (\sqrt{x})'=\frac{1}{2\sqrt{x}}\\ (cosx)'=-sinx\\ (u^{n})'=n\cdot u^{n-1}\cdot u'\\](https://tex.z-dn.net/?f=%28u-v%29%27%3Du%27v-uv%27%5C%5C+%28cx%29%27%3Dc%5C%5C+%28%5Cfrac%7Bu%7D%7Bv%7D%29%27%3D%5Cfrac%7Bu%27v-uv%27%7D%7Bv%5E%7B2%7D%7D%5C%5C+%28%5Csqrt%7Bx%7D%29%27%3D%5Cfrac%7B1%7D%7B2%5Csqrt%7Bx%7D%7D%5C%5C+%28cosx%29%27%3D-sinx%5C%5C+%28u%5E%7Bn%7D%29%27%3Dn%5Ccdot+u%5E%7Bn-1%7D%5Ccdot+u%27%5C%5C+)
1.
f (x) = 4x - \frac{2}{\sqrt{x}}\\ f' (x) = (4x - \frac{2}{\sqrt{x}})' = {4x}'-(\frac{2}{\sqrt{x}})'=4 - \frac{2' \cdot \sqrt{x}-2\cdot (\sqrt{x})'}{(\sqrt{x})^{2}}=\\ =4 - \frac{-2\cdot \frac{1}{2\sqrt{x}}}{(\sqrt{x})^{2}}=4 - (- \frac{\frac{1}{\sqrt{x}}}{(\sqrt{x})^{2}})=4 + \frac{1}{\sqrt{x}}:\frac{(\sqrt{x})^{2}}{1}=4+\frac{1}{\sqrt{x}}\cdot \frac{1}{x}=\\ =4+\frac{1}{\sqrt{x^{3}}}" alt="f (x) = 4x - \frac{2}{\sqrt{x}}\\ f' (x) = (4x - \frac{2}{\sqrt{x}})' = {4x}'-(\frac{2}{\sqrt{x}})'=4 - \frac{2' \cdot \sqrt{x}-2\cdot (\sqrt{x})'}{(\sqrt{x})^{2}}=\\ =4 - \frac{-2\cdot \frac{1}{2\sqrt{x}}}{(\sqrt{x})^{2}}=4 - (- \frac{\frac{1}{\sqrt{x}}}{(\sqrt{x})^{2}})=4 + \frac{1}{\sqrt{x}}:\frac{(\sqrt{x})^{2}}{1}=4+\frac{1}{\sqrt{x}}\cdot \frac{1}{x}=\\ =4+\frac{1}{\sqrt{x^{3}}}" align="absmiddle" class="latex-formula">
2. ![y = cos^{2}x\\ y' = (cos^{2}x)'=2\cdot cosx \cdot (- sinx)=-2cosx\cdot sinx\\ y = cos^{2}x\\ y' = (cos^{2}x)'=2\cdot cosx \cdot (- sinx)=-2cosx\cdot sinx\\](https://tex.z-dn.net/?f=y+%3D+cos%5E%7B2%7Dx%5C%5C+y%27+%3D+%28cos%5E%7B2%7Dx%29%27%3D2%5Ccdot+cosx+%5Ccdot+%28-+sinx%29%3D-2cosx%5Ccdot+sinx%5C%5C+)